A new milk-clotting enzyme produced by Bacillus sp. P45 applied in cream cheese development - Lemes, Ailton Cesar (2016)
The growing demand for natural coagulants led to an increased necessity for rennet substitutes, promoting a search for new sources of proteases with coagulant properties. The aim of this study was to investigate the application of a bacterial enzyme as a novel milk-clotting protease in the development of cream cheese enriched with chia and quinoa flour. At the concentration of 30 mg/mL, the milk-clotting strength was similar to that observed for commercial chymosin, demonstrating the enzyme ability to catalyze the hydrolysis of milk casein. The cheese developed showed high water retention (≥99.0%) and consequently low syneresis process. The results indicate that the product made using the enzyme showed adequate sanitary conditions and technological characteristics indicated that the product is highly stable and viable.